Therapeutic response of HIV-1 subtype C in African patients coinfected with either Mycobacterium tuberculosis or human herpesvirus-8. - Cassol, Edana; Page, Taryn; Mosam, Anisa; Friedland, Gerald; Jack, Chris; Lalloo, Umesh; Kopetka, Joe; Patterson, Bruce; Esterhuizen, Tonya; Coovadia, Hoosen M (The Journal of infectious diseases, 2005)
A potential confounding factor in the treatment of human immunodeficiency virus (HIV) infection in Africa is the frequent occurrence of opportunistic infections (OIs). OI-induced immune activation can interfere with HIV-1 clearance by increasing viral replication and target cell availability.
Keywords: Adolescent; Adult; AIDS-Related Opportunistic Infections; Anti-HIV Agents; CD4 Lymphocyte Count; Drug Therapy, Combination; Female; Herpesvirus 8, Human; HIV Infections; HIV-1; Humans; Male; Middle Aged; Mycobacterium tuberculosis; Reverse Transcriptase Inhibitors; RNA, Viral; Sarcoma, Kaposi; Treatment Outcome; Tuberculosis, Pulmonary; Viral Load